2017
DOI: 10.1016/j.jvolgeores.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Geothermal potential and origin of natural thermal fluids in the northern Lake Abaya area, Main Ethiopian Rift, East Africa

Abstract: In this study, the occurrence, chemical composition, origin and geothermal significance of thermal springs and fumaroles naturally discharging in the area located north of the Lake Abaya (western margin of the Main Ethiopian Rift, East Africa) are reviewed in relation with recent tectonics. All thermal springs showed a dominantly Na-HCO 3 composition, consistent with observations dating from at least 1972, and most of them displayed a narrow range of δD and δ 18 O isotopic compositions for water similar to reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
28
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 48 publications
9
28
2
1
Order By: Relevance
“…Cross sections through cluster 1 (Figure 10), which lies at the boundary between the central and southern MER (Figure 1), do not unambiguously delineate a simple, single fault plane associated with the western border fault system of the MER. Minissale et al (2017) found that the chemistry of thermal springs and fumaroles discharging naturally in the area immediately to the north of Lake Abaya is dominated by a 2 CO -rich gas phase and discharges along the active faults bordering the western edge of the MER. Cluster 1 is therefore readily explained by deformation associated with upper crustal magmatic fluid migration, akin to the central and northern MER (e.g., Keir et al, 2006).…”
Section: Implications For Extension and Magmatism In The Southern Mermentioning
confidence: 99%
“…Cross sections through cluster 1 (Figure 10), which lies at the boundary between the central and southern MER (Figure 1), do not unambiguously delineate a simple, single fault plane associated with the western border fault system of the MER. Minissale et al (2017) found that the chemistry of thermal springs and fumaroles discharging naturally in the area immediately to the north of Lake Abaya is dominated by a 2 CO -rich gas phase and discharges along the active faults bordering the western edge of the MER. Cluster 1 is therefore readily explained by deformation associated with upper crustal magmatic fluid migration, akin to the central and northern MER (e.g., Keir et al, 2006).…”
Section: Implications For Extension and Magmatism In The Southern Mermentioning
confidence: 99%
“…In relation to the active fault zone, many thermal springs emerge in the area particularly in tectonically active northern Abaya in the rift floor. The thermal springs discharge within the rift floor along the north -northeast to south-southwest (NNE-SSW) trending faults [42] that emerge at varying elevations. Thermal springs in the northern lake Abaya area characterized by a temperature ranging from 35 to 95 • C and Na-HCO 3 type [42] with a TDS in the range of 1000-2500 mg/L.…”
Section: Geological and Hydrogeological Settingsmentioning
confidence: 99%
“…Hydrogeochemical behaviors of thermal and non-thermal groundwater can be characterized using plots of various ions contents against electric conductivity or salinity as TDS (Delalande et al, 2008;Minissale et al, 2017). In Fig.…”
Section: Insights On Recharge Source and Water-rock Interactionsmentioning
confidence: 99%